Lynn K. Nyhart, Biology Takes Form. Animal Morphology and the German Universities - Elías José Palti (Prismas, 1999)
Lynn K. Nyhart, Biology Takes Form. Animal Morphology and the German Universities, 1800-1900, Chicago y Londres, The University of Chicago Press, 1995, 361 páginas (más apéndices, bibliografía e índice)